1999
DOI: 10.1046/j.1440-1614.1999.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Absconding behaviour: an exploratory investigation in an acute inpatient unit

Abstract: Situational and environmental factors are more likely than patient characteristics to be predictive of absconding behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 10 publications
4
44
5
Order By: Relevance
“…In the present study, the risk of absconding in younger patients was higher than older patients, which is similar to previous studies (1,8,14,26). In this regard, in a review study, absconding patients were younger than others (18).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the risk of absconding in younger patients was higher than older patients, which is similar to previous studies (1,8,14,26). In this regard, in a review study, absconding patients were younger than others (18).…”
Section: Discussionsupporting
confidence: 91%
“…From the available literature, the broad profile of patients that abscond are young, detained males diagnosed with Schizophrenia (Farragher, Gannon & Ahmad 1996;Quinsey & Coleman 1997;Bowers et al 1999a;Meehan, Morrison & McDougall 1999;Bowers et al 2000;Bowers, Alexander & Gaskell 2003;Carr 2006) and this research is in keeping with the profile of patients that abscond previously identified. Patients from a CALD background diagnosed with schizophrenic disorders who absconded were younger than their Caucasian counterparts.…”
Section: Discussionsupporting
confidence: 64%
“…Briefly, they include the lack of a comparison sample to draw aetiological conclusions; obtaining information from case records and clinical judgements, rather than standardised methods; and the potential for bias from clinicians' awareness of patient outcome (particularly on variables such as estimation of risk). Further, we could not establish if patients had previously absconded from the ward, an apparent risk factor for future absconding [19,21], nor could we ascertain the length of time between leaving the ward and suicide unless the death occurred within a week of admission.…”
Section: Discussionmentioning
confidence: 99%